Risk factors responsible for lower respiratory tract infections in children aged under five: a hospital based study - Seth, Samrita; Ganguly, Sristi; Satpathy, Saroj K. (International Journal of Contemporary Pediatrics, 2020)
Background: Lower respiratory tract infections (LRTI) contribute significantly in terms of hospital admission and mortality. Along with attempts to improve treatment modalities, it is imperative to identify risk factors that will aid in prevention of these infections. Methods: This was a case-control study done in tertiary care hospital, Cuttack, enrolling inpatients between 2 months to 5 years with symptoms suggestive of LRTI as cases. Those with tuberculosis, aspiration pneumonia, asthma and nosocomial infections were excluded. After obtaining consent, questionnaire was administered to parents, regarding their socio-demographic and other relevant details. Data analysis was done using statistical software Epi Info™, version 6 and association of each variable with LRTI assessed with chi-square test. Results: A total of 314 children were enrolled in the study, with 158 being cases. The case-fatality rate was 23% and 53.8% suffered from complications, the most common being respiratory failure. A significant association was seen between LRTI and social variables namely maternal literacy(p-value<0.005), socioeconomic status (p-value<0.001) and number of children (p-value<0.001), housing pattern (p-value<0.001), fuel used at home (p-value=0.003), ventilation adequacy (p-value=0.004), presence of separate kitchen at home (p-value=0.0009) and presence of overcrowding (p-value<0.001) and individual factors improper breastfeeding(p-value<0.005) and weaning(p-value=0.03), malnutrition (p-value<0.001), vitamin A deficiency(p-value=0.03) and history of respiratory infection in mother (p-value=0.025) or siblings(p-value=0.048). Conclusions: The burden of lower respiratory tract infections can be substantially reduced by prevention using the identification of risk factors such as housing patterns, education of parents and improved nutrition of the children, and measures to combat the same, at each level.